DEVELOPING ASSESSMENT OF TEACHING ASSISTANCE PROGRAM IN STBA JIA - Winda Lutfiyanti; Ade Surista; Esterria Romauli (IKIP Siliwangi, 2024)
This research aimed to design and develop an assessment design commensurate with English for Teaching along with Applied English, English Critical Thinking, Practice, and Report courses in English Literature Department of STBA JIA. Using Research and Development referring to ADDIE model proposed by Branch (2010), this research includes analyze, design, develop, implement, and evaluate. The instruments used are interview, questionnaire, and observation. The assessment design covers five mechanism including formulation of learning targets, selection and form assessment instruments, implementation of the assessment, procedure of measurement, and report of assessment result.